Ulul Albab Dalam Kehidupan Manusia (Studi Sematik Dalam Al-Qur’an) - Jumi Yanti (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2024)
Ulul albab in the Qur'an discusses people who use reason to think and recite remembrance of natural phenomena and the power of Allah SWT. There are sixteen derivation of ulul albab verses in the Qur'an, which is why this research uses a thematic interpretation study. This research formulates how to understand the characteristics of ulul albab in the Qur'an? This research method uses thematic analysis with a philosophical and exegetical approach. This research is a literature review which is carried out by collecting data and analyzing data according to primary and secondary sources. For this reason, the author tries to know and understand the concept of ulul albab contained in it. This article is a thematic commentary, where the author tries to collect verses that have the same theme, namely ulul albab verses, then traces them to classical and contemporary tafsir books. This thematic interpretation study was carried out to understand the concept of ulul albâb as a whole in the view of the Qur'an.Keywords: Semantics of the Qur'an; Ulul Albab Thematic Tafsir.